Evaluation of Peripapillary and Subfoveal Choroid Thickness in Asymptomatic Carotid Artery Stenosis - Turan-Vural E (Dove Medical Press, 2020)
Ece Turan-Vural,1 Unsal Vural2 1Ophthalmology Clinic, Haydarpasa Numune Training and Research Hospital, Istanbul, Turkey; 2Cardiovascular Surgery Clinic, Siyami Ersek Training and Research Hospital, Istanbul, TurkeyCorrespondence: Ece Turan-VuralHaydarpasa Egitim ve Arastırma Hastanesi Tibbiye Caddesi, Göz Klinigi No: 40, Uskudar/Istanbul 34668, TurkeyTel +90 505 400 46 28Fax +90 216 337 78 77Email dreceturan76@gmail.comObjective: In this study, it aims to investigate the effect of asymptomatic carotid artery stenosis on peripapillary and subfoveal choroid thickness using enhanced depth imaging optical coherence tomography.Patients and Methods: While investigating for coronary artery disease, 76 patients with asymptomatic carotid artery stenosis and 35 patients with normal carotid artery (total = 111) were evaluated. Patients according to the degree of stenosis were divided into four categories as non-stenosis (n = 35), mild (n = 26), moderate (n = 27) and severe stenosis (n = 23). Subfoveal and peripapillary choroid thickness, ocular perfusion and intraocular pressures of all patients were measured using a Fourier-domain optical coherence tomography after general ophthalmological examination. In addition, hypertension, hyperlipidemia, and whether there is a relationship between smoking status and choroid thickness was compared.Results: As the degree of carotid artery stenosis increased, subfoveal and peripapillary choroidal thickness decreased significantly. However, no changes were detected in ocular perfusion and intraocular pressure values (p=0.935, p=0.519). Decrease in peripapillary and subfoveal choroid thickness values was found to be particularly between the group with severe stenosis and the group with control and mild stenosis (p = 0.003, p = 0.001). In addition, as the degree of carotid stenosis increased in patients with hypertension and smoking, peripapillary choroid thickness was found to be thinner (p=0.003).Conclusion: We believe that the possibility of carotid artery stenosis should be considered in cases with decreased choroid thickness. In addition, we think that even if it is asymptomatic, in cases with severe carotid stenosis, in the presence of choroidal thinning, a chance of surgical intervention should be given to the stenosis.Keywords: carotid artery stenosis, subfoveal choroid thickness, peripapillary choroid thickness, enhanced depth imaging optical coherence tomography